2009
DOI: 10.1124/jpet.109.162149
|View full text |Cite
|
Sign up to set email alerts
|

Clarithromycin Inhibits Type A Seasonal Influenza Virus Infection in Human Airway Epithelial Cells

Abstract: Human influenza viruses attach to sialic acid with an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 35 publications
2
68
2
1
Order By: Relevance
“…We also reported previously that a macrolide antibiotic, clarithromycin, and L-carbocisteine inhibit seasonal influenza virus infection by reducing the expression level of its receptor SA␣2,6Gal and by reducing the number of acidic endosomes in human tracheal epithelial cells (44,45). In this study, we demonstrated that LVFX reduces the ICAM-1 expression level and slightly but significantly reduces the number of acidic endosomes.…”
Section: Discussionsupporting
confidence: 57%
“…We also reported previously that a macrolide antibiotic, clarithromycin, and L-carbocisteine inhibit seasonal influenza virus infection by reducing the expression level of its receptor SA␣2,6Gal and by reducing the number of acidic endosomes in human tracheal epithelial cells (44,45). In this study, we demonstrated that LVFX reduces the ICAM-1 expression level and slightly but significantly reduces the number of acidic endosomes.…”
Section: Discussionsupporting
confidence: 57%
“…DAS181 is currently in Phase II development (27). Clarithromycin, a macrolide antibiotic used to treat tonsillitis and pharyngitis, has potential as an influenza therapeutic; it reduces the expression of sialic acid receptors on the surface of airway epithelial cells and decreases the number of acidic endosomes in the cell, reducing viral endocytosis (31).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, we have also reported that 75% of patients treated with the combination of CAM and OSV showed increases in S-IgA production to levels similar to those seen in patients treated with CAM alone (37). Others have also reported that CAM acted on the viral replication cycles, resulting in inhibition of progeny virus production in vitro (25,26), and modulated airway inflammation in IAV infection by reduction of the viral receptor, sialic acid with an ␣2,6 linkage on the airway epithelial cells, through inhibition of nuclear factor kappa B (NF-B) expression and increase in intraendosomal pH (45).…”
mentioning
confidence: 93%
“…At days 8 and 12 after infection, nasal washes (NWs), bronchoalveolar fluids (BALF), and plasma were collected as described previously (27,45) and subjected to enzyme-linked immunosorbent assay (ELISA) to determine anti IAV-specific S-IgA and IgG levels (27,33,39). Mononuclear cells isolated from the MeLNs, lungs, NPs, and spleen were subjected to an enzyme-linked immunosorbent spot (ELISPOT) assay to determine the numbers of IgA and IgG antibody (Ab)-forming cells (AFCs), as described previously (15,17,39).…”
Section: Methodsmentioning
confidence: 99%